A Q420 grade low-temperature impact-resistant super-large beam type specification hot-rolled H-shaped steel and a production method thereof
Patent Information
- Application Number
- CN202510698639.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-05-28
AI Technical Summary
该产品主要通过添加Cr、Ni、Cu元素提高产品的耐腐蚀性能,且产品主要通过不同规格异形坯轧制不同规格成品,但是总体翼缘宽度限制在300mm以下,且合金成本较高
[0029] Compared with existing technologies, this invention, through component design and a reasonable rolling reduction ratio, meets the shape control technology for the biphasic microstructure transformation process and flatness deviation in actual production. Combined with actual on-site production process operations, it realizes the production of high-strength hot-rolled H-beam products through a process of billet rolling + universal finishing rolling + cooling control. The produced products are ultra-large beam-shaped products with flange thickness ranging from 30mm to 80mm, web height H ranging from 800mm to 1200mm, and a web height H/flange width B ratio ranging from 2.2 to 3.3. Their yield strength is not less than 420MPa, tensile strength is 520-680MPa, yield strength ratio does not exceed 0.78, elongation after fracture is not less than 20%, longitudinal impact energy value at -20℃ is not less than 100J, and transverse impact energy value at -20℃ is not less than 80J. This meets the requirements of the domestic bridge and building structure industry for ultra-large beam-shaped specifications of Q420 grade that can withstand low-temperature impact at -20℃.
Smart Images

Figure CN120464939B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal material production technology, specifically relating to a Q420 grade hot-rolled H-beam with ultra-large beam-shaped specifications that can withstand low-temperature impact of -20℃ and its production method. Background Technology
[0002] Currently, commonly used structural steel products in bridge and building structures include H-beams, angle steel, and channel steel, with strength primarily at the 355MPa level. However, with the increasing longitudinal height of building structures, hot-rolled H-beams with ultra-high web height and ultra-wide web width are becoming the future development direction for bridges and buildings. Among them, ultra-high web H-beams are widely used in bridge and building structure markets due to their environmental friendliness, cost-effectiveness, and practicality. Considering the load-bearing capacity of bridge structures and building sections, large-sized H-beams (welded or hot-rolled) are typically used for continuous erection. These ultra-large H-beams not only reduce the number of pier supports, effectively reducing construction and cost, but also reduce the size of bridge cap beams and columns, decreasing the actual assembly plant area and accelerating the bridge construction cycle.
[0003] The patent, published on November 4, 2015, with publication number CN105018839A and titled "A 420MPa Grade High-Performance Seismic-Resistant H-Beam and Its Preparation Method," discloses the following steel composition by mass percentage: C: 0.15–0.18 wt%, Si: 0.30–0.45 wt%, Mn: 1.35–1.55 wt%, V: 0.070–0.090 wt%, P: ≤0.015 wt%, S: ≤0.020 wt%, with the remainder being Fe and unavoidable impurities. The preparation method includes steelmaking, deoxidation and alloying, LF furnace refining, steel casting, and post-treatment steps. Its smelting process employs a nitrogen-rich vanadium microalloying process, effectively refining austenite grains. Increasing the nitrogen content during smelting promotes the formation of vanadium carbonitrides, which are dispersed at grain boundaries, further refining the austenite grains through nucleation. Through rolling, controlled cooling, and rapid cooling processes, the H-beams achieve excellent shape and surface quality, eliminate processing stress, and improve performance. However, this product primarily utilizes a universal 10-stand continuous rolling mill process, suitable for rolling small rectangular billets into finished products with a diameter of 20mm or less, and is only applicable to small-scale construction.
[0004] A patent published on March 16, 2016, with publication number CN105401075A and titled "A 420MPa Grade H-beam and its Preparation Method," discloses the following steel composition by mass percentage: C 0.11-0.15%, Si 0.20-0.35%, Mn 1.35-1.50%, P≤0.035%, S≤0.025%, Cu 0.25-0.30%, Cr 0.40-0.45%, Ni 0.20-0.30%, Nb 0.20-0.30%, with the remainder being iron and trace impurities. Through optimized composition design and controlled heating, it is possible to produce 420MPa grade H-beams with a low yield strength ratio under high final rolling temperature conditions, and mass production of this type of product has been achieved. Its yield strength is greater than 427MPa, tensile strength is greater than 641MPa, and yield strength ratio is 0.64-0.67. However, this product mainly improves its strength by adding alloys such as Cr, Ni, and Nb, resulting in high alloy costs and small rolling specifications, thus limiting its application range.
[0005] The patent document published on March 3, 2023, with publication number CN115725901 A and titled "A Thick-Spec High-Strength Weather-Resistant and Seismic-Resistant Hot-Rolled H-Beam for Building Steel Structures," discloses the following steel composition by mass percentage: C 0.05%-0.15%, Si 0.25%-0.50%, Mn 1.10%-1.40%, P≤0.030%, S≤0.010%, V 0.10%-0.15%, Cu 0.20%-0.35%, Ni 0.20%-0.35%, Cr 0.30%-0.45%, N 0.008%-0.015%, with the remainder being Fe and impurities, totaling 100% by mass; carbon equivalent (CEN) ≤0.36%; corrosion resistance index (I) ≥6.0; and the yield strength R of the H-beam. eL ≥420MPa, tensile strength R m ≥520MPa, yield strength ratio ≤0.80, impact toughness KV2≥80J at 0℃. This product mainly improves its corrosion resistance by adding Cr, Ni, and Cu elements. The product is mainly rolled into finished products of different specifications from irregularly shaped billets, but the overall flange width is limited to less than 300mm, and the alloy cost is relatively high.
[0006] In summary, while significant technological advancements have been made in the development of 420MPa grade hot-rolled H-beams, the processes and performance of some products remain limited by production equipment and on-site conditions to meet the current application demands in bridge and building structures. Therefore, it is essential to develop hot-rolled H-beams of Q420 grade with ultra-large beam-shaped specifications, taking into account existing production equipment and practical production realities. Summary of the Invention
[0007] The purpose of this invention is to provide a Q420 grade hot-rolled H-beam with a low-temperature impact resistance of -20℃ for ultra-large beams and its production method. Through composition and process design, the product has a yield strength ≥420MPa, tensile strength 520~680MPa, yield ratio ≤0.78, elongation after fracture ≥20%, longitudinal impact energy value ≥100J at -20℃, and transverse impact energy value ≥80J at -20℃, meeting the requirements of the domestic bridge and building structure industry for Q420 grade ultra-large beams with a low-temperature impact resistance of -20℃. Furthermore, it does not use precious metals such as Cr and Ni, resulting in low cost.
[0008] The specific technical solution of this invention is as follows:
[0009] A Q420 grade hot-rolled H-beam of extra-large beam type with low-temperature impact resistance of -20℃, comprising the following composition by mass percentage: C: 0.16%~0.20%, Si: 0.15%~0.28%, Mn: 1.30%~1.60%, P: ≤0.025%, S: ≤0.015%, V: 0.060%~0.110%, Als: 0.005%~0.020%, wherein 2.0≤VN / VFe≤3.5, and the remainder is Fe and trace residual elements.
[0010] The flange thickness of the Q420 grade ultra-large beam-shaped hot-rolled H-beams with low-temperature impact resistance of -20℃ ranges from 30mm to 80mm, the web height H ranges from 800mm to 1200mm, and the ratio of web height H to flange width B is H / B = 2.2 to 3.3.
[0011] The Q420 grade ultra-large beam-shaped hot-rolled H-beams with low-temperature impact resistance of -20℃ are designed with universal rolling process. The finished product has a microstructure of ferrite + pearlite, with the ferrite microstructure area accounting for ≥60% and the ferrite grain size grade being 9.5 or above.
[0012] The Q420 grade hot-rolled H-beams of ultra-large beam type with -20℃ low-temperature impact resistance have a yield strength ≥420MPa, tensile strength 520~680MPa, yield-to-tensile ratio ≤0.78, elongation after fracture ≥20%, longitudinal impact energy value ≥100J at -20℃, and transverse impact energy value ≥80J at -20℃. This meets the requirements of the domestic bridge and building structure industry for Q420 grade ultra-large beam type with -20℃ low-temperature impact resistance.
[0013] This invention provides a method for producing ultra-large beam-shaped hot-rolled H-beams of Q420 grade with low-temperature impact resistance up to -20℃, comprising the following process flow:
[0014] Billet heating → billet rolling → universal precision rolling → air cooling.
[0015] The billet heating process involves heating the billet in the furnace at a temperature of 1235℃~1265℃ in the heating section and 1225℃~1255℃ in the soaking section, with the soaking time lasting 35min~55min. The total furnace time is 150min~180min, ensuring that the initial austenite grain size is not lower than grade 7.0. To prevent excessively long furnace time from increasing energy consumption and causing coarse initial microstructure, the billet should not be in the furnace for too long.
[0016] Before rolling in the billet mill, high-pressure water descaling should be carried out to break the oxide layer on the surface of the billet and blow away the attached fine iron oxide scale.
[0017] The initial rolling process involves an initial rolling temperature of 1150℃ to 1180℃ and a final rolling temperature of not less than 1100℃. This ensures that the temperature before the initial rolling stage is higher than the complete recrystallization temperature of austenite. Throughout the initial rolling stage, 30% to 40% of the cross-sectional compression ratio and 50% to 70% of the flange compression ratio are achieved, promoting the recrystallization of the original austenite grains and providing the original refined microstructure for subsequent secondary compression deformation.
[0018] The universal finishing rolling process involves an initial rolling temperature not exceeding 1100℃. This process primarily ensures that the large deformation during continuous rolling achieves compression changes in the flange thickness of the irregularly shaped billet, guaranteeing a flange thickness compression ratio of 30%–50% throughout the finishing rolling stage. Specifically, the rolling speed range for the first 45% or more flange reduction passes in the universal stage is 2.5–3.5 m / s; the rolling speed range for the middle 40% or more flange reduction passes is 4.5–5.5 m / s, with at least 15% of the flange reduction within each reduction pass controlled at a temperature between 920 and 950℃; and the rolling speed range for the last 15% or less flange reduction passes is 2.5–3.5 m / s. Through this allocation of reduction passes and the coordinated control of rolling speed and temperature, the strength and plasticity of the hot-rolled H-beam are improved.
[0019] Air cooling: After rolling, the rolled piece is transported to the cooling bed by the transport roller conveyor and air-cooled to room temperature.
[0020] The design concept of this invention is as follows:
[0021] Carbon (C): Carbon is the most basic element in steel. Through its combination with other elements, it plays a significant role in improving the strength of steel. In order to meet the requirements of high strength level, and considering the high strength requirements of the product, the lower limit is set at 0.16wt%. Considering the difficulty of controlling the steelmaking process and the adverse effects on the plasticity of the material caused by excessive carbon content, the upper limit is set at 0.20wt%.
[0022] Silicon (Si): It exists in steel in solid solution form and has a strong solid solution strengthening effect, which can significantly strengthen ferrite. To obtain high strength, the lower limit is set at 0.15 wt%. However, when Si is higher than 0.30%, the toughness and plasticity of steel decrease significantly, especially the transverse impact toughness. Considering the actual control requirements, the upper limit is set at 0.28 wt%.
[0023] Manganese (Mn): Effectively inhibits the transformation of ferrite to pearlite, greatly improving the low-temperature toughness of the material. It can also lower the phase transformation temperature, which is beneficial for the transformation of austenite under low-temperature conditions. However, excessive manganese content can cause segregation defects inside the cast billet; therefore, the Mn content should be controlled between 1.30 and 1.60 wt%.
[0024] Phosphorus (P): It tends to segregate in steel, which greatly reduces the plasticity and toughness of the steel and has a certain impact on the surface quality of the steel. Considering the difficulty of removing P in the steelmaking process, the upper limit is set at 0.025 wt%.
[0025] Sulfur (S): It has a significant impact on the toughness of steel. It is easy to accumulate and segregate within and at the boundaries of grains. In particular, it readily forms MnS inclusions with manganese, making the matrix structure of the material prone to the boundary initiation of cracks. Considering the difficulty of desulfurization in the steelmaking process, the upper limit is set at 0.015 wt%.
[0026] Vanadium (V): Vanadium is one of the most important microalloying elements in steel, exhibiting significant grain refinement strengthening, precipitation strengthening, and sedimentation strengthening effects. Vanadium readily forms carbonitrides with nitrogen, effectively preventing excessive grain growth, promoting the transformation of austenite to ferrite, facilitating the precipitation of soft and tough phases, and improving the low-temperature toughness of the material. Furthermore, during the post-rolling cooling process, the precipitation of carbonitrides plays a certain strengthening role. For high-strength steel, considering the strengthening effect of vanadium, a lower limit of 0.060 wt% is set, especially when the product thickness is large and the flange compression ratio is small, requiring microalloying to improve product strength. However, due to the influence of vanadium precipitation concentration, excessively high vanadium content cannot achieve the precipitation strengthening effect and has no significant impact on the actual mechanical properties of the steel. Moreover, excessively high vanadium alloy content leads to a significant increase in production costs; therefore, an upper limit of 0.110 wt% is set. Considering the cost of the alloy and the nitrogen fixation effect, vanadium is added in a VN / VFe ratio. To ensure the precipitation effect of VN compounds, the VN / VFe alloy ratio should be no less than 2.0. At the same time, to save production costs, the actual VN alloy input should not be too high. Therefore, the V content ratio should meet the requirement of 2.0≤VN / VFe≤3.5.
[0027] Aluminum (Als): A strong oxidizing element that can be used for deoxidation in steelmaking. In addition, aluminum can precipitate in combination with nitrogen, refining austenite grains; the lower limit is set at 0.005 wt%. However, excessive aluminum content significantly reduces the plasticity and toughness of the material, and in continuous casting of irregularly shaped billets, it easily causes brittle defects, leading to leaks and affecting production safety; the upper limit is set at 0.020 wt%.
[0028] Because large-size products have large cross-sectional dimensions, especially thick-size products with small flange compression ratios, it is difficult to achieve grain refinement through large compression. Therefore, in terms of composition design, refining the original size of austenite grains is beneficial to subsequent microstructure transformation to achieve the effect of grain refinement. At the same time, with the addition of certain microalloying, second-phase particles are precipitated to achieve precipitation strengthening effect, thereby improving the strength and toughness of the material.
[0029] Compared with existing technologies, this invention, through component design and a reasonable rolling reduction ratio, meets the shape control technology for the biphasic microstructure transformation process and flatness deviation in actual production. Combined with actual on-site production process operations, it realizes the production of high-strength hot-rolled H-beam products through a process of billet rolling + universal finishing rolling + cooling control. The produced products are ultra-large beam-shaped products with flange thickness ranging from 30mm to 80mm, web height H ranging from 800mm to 1200mm, and a web height H / flange width B ratio ranging from 2.2 to 3.3. Their yield strength is not less than 420MPa, tensile strength is 520-680MPa, yield strength ratio does not exceed 0.78, elongation after fracture is not less than 20%, longitudinal impact energy value at -20℃ is not less than 100J, and transverse impact energy value at -20℃ is not less than 80J. This meets the requirements of the domestic bridge and building structure industry for ultra-large beam-shaped specifications of Q420 grade that can withstand low-temperature impact at -20℃. Attached Figure Description
[0030] Figure 1 The microstructure of the H-beam obtained in Example 1 is ferrite + pearlite;
[0031] Figure 2 The microstructure of the H-beam obtained in Example 4 is ferrite + pearlite. Detailed Implementation
[0032] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0033] Examples 1-8
[0034] A Q420 grade, ultra-large beam-shaped hot-rolled H-beam with low-temperature impact resistance up to -20℃, comprises the following composition by weight percentage as shown in Table 1. The balance not shown in Table 1 represents Fe and unavoidable impurities.
[0035] Comparative Examples 1-7
[0036] A hot-rolled H-beam comprises the following composition by weight percentage as shown in Table 1. The balance not shown in Table 1 is Fe and unavoidable impurities.
[0037] Table 1. Composition of steels in each embodiment and comparative example.
[0038]
[0039]
[0040] Example 1 and Comparative Example 1, Example 3 and Comparative Example 2, Example 4 and Comparative Example 3, Example 5 and Comparative Example 4, and Example 7 and Comparative Example 5 have the same components.
[0041] The steels in the above embodiments and comparative examples are produced according to the following process: hot metal pretreatment → converter smelting → argon blowing refining → LF refining → special-shaped billet casting → billet heating → billet rolling → universal precision rolling → air cooling on cooling bed → length straightening → bundling.
[0042] Billet heating: The billet is heated to 1235℃~1265℃ in the heating section and 1225℃~1255℃ in the soaking section of the furnace, with the soaking time being 35min~55min. The total furnace time is 150min~180min, ensuring that the initial austenite grain size is not lower than grade 7.0. To prevent excessively long furnace time from increasing energy consumption and causing coarse initial microstructure, the billet should not be in the furnace for too long.
[0043] Opening rolling: Before rolling on the opening mill, high-pressure water descaling should be performed to break the oxide layer on the surface of the billet and simultaneously blow away the attached fine iron oxide scale. The opening rolling temperature is 1150℃~1180℃, and the final rolling temperature is not lower than 1100℃. This ensures that the temperature before the opening rolling section is higher than the complete recrystallization temperature of austenite. Throughout the opening stage, 30%~40% of the cross-sectional compression ratio and 50%~70% of the flange compression ratio are achieved, promoting the recrystallization of the original austenite grains and providing the original refined microstructure for subsequent secondary reduction deformation.
[0044] Universal finishing rolling: The initial rolling temperature does not exceed 1100℃. This process mainly ensures that the large deformation during rolling in the continuous rolling stage achieves the compression change of the flange thickness of the irregular billet. The flange thickness compression ratio is ensured to be 30%–50% of the billet flange thickness throughout the finishing rolling stage. Specifically, the rolling speed range for the first 45% or more flange reduction passes in the universal stage is 2.5–3.5 m / s, the rolling speed range for the middle 40% or more flange reduction passes is 4.5–5.5 m / s, and the temperature of at least 15% of the flange reduction within each reduction pass is controlled within the range of 920–950℃. The rolling speed range for the last 15% or less of the flange reduction passes is 2.5–3.5 m / s. Through the above-mentioned reduction pass allocation and the matching control of rolling speed and rolling temperature, the strength and plasticity of the hot-rolled H-beam are improved.
[0045] Air cooling: After rolling, the rolled piece is transported to the cooling bed by the transport roller conveyor and air-cooled to room temperature.
[0046] Length straightening: The finished products on the cooling bed are cut to multiples or fixed lengths, and the cut products are transported to the straightening machine to straighten the shape of the finished products.
[0047] Bundling: Bundling and packaging finished products of fixed length and storing them in the warehouse for shipment.
[0048] The main process parameters for each embodiment and comparative example are shown in Table 2.
[0049] Table 2. Main rolling parameters for each embodiment and comparative example.
[0050]
[0051]
[0052] In Table 2, the first 45% or more of the flange compression process in the universal stage is stage I; the middle 40% or more of the flange compression process is stage II; and the last 15% or less of the flange compression process is stage III.
[0053] The microstructure and properties of the H-beams in each embodiment and comparative example were tested (mechanical properties were performed according to GB / T1591-2018, sampling methods according to GB / T 2975, and microstructure tests according to GB / T 6394-2017 and GB / T13298-2015; other standard systems may also be selected according to the corresponding steel grade products), and the results are shown in Tables 3 and 4.
[0054] Table 3. Microstructure of H-beams in each embodiment and comparative example
[0055]
[0056]
[0057] In Table 3, F represents ferrite and P represents pearlite.
[0058] Table 4 Mechanical properties of H-beams in each embodiment and comparative example
[0059]
[0060] As can be seen from the embodiments in Tables 1 to 4, the H-beam products produced by the method described in this invention have a yield strength of 421 MPa to 445 MPa, a tensile strength of 553 MPa to 613 MPa, a yield-to-tensile ratio of 0.71 to 0.78, an elongation of 22% to 26.0%, a longitudinal impact energy of 102 J to 151 J at -20℃, and a transverse impact energy of 86 J to 112 J at -20℃.
[0061] The data underlined above do not meet the requirements of this invention. A detailed comparison is shown in Table 5 below.
[0062] Table 5. Comparative Examples
[0063]
[0064] The above description of the embodiments is intended to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A Q420 grade hot-rolled H-beam with ultra-large beam-shaped specifications resistant to low-temperature impact at -20℃, characterized in that, The Q420 grade ultra-large beam-shaped hot-rolled H-beams with low-temperature impact resistance up to -20℃ comprise the following composition by weight percentage: C: 0.16%~0.20%, Si: 0.15%~0.28%, Mn: 1.30%~1.60%, P: ≤0.025%, S: ≤0.015%, V: 0.060%~0.110%, Als: 0.005%~0.020%, of which 2.0≤VN / VFe≤3.5, and the remainder is Fe and trace residual elements; The flange thickness of the Q420 grade ultra-large beam-shaped hot-rolled H-beam with low temperature impact resistance of -20℃ is in the range of 30mm~80mm, the web height H is in the range of 800mm~1200mm, and the ratio of web height H to flange width B is H / B=2.2~3.
3. The microstructure of the Q420 grade ultra-large beam-shaped hot-rolled H-beam with low-temperature impact resistance of -20℃ is ferrite + pearlite, with ferrite accounting for ≥60% and ferrite grain size grade of 9.5 or above. The Q420 grade hot-rolled H-beams of ultra-large beam type with low-temperature impact resistance of -20℃ have a yield strength ≥420MPa, tensile strength 520~680 MPa, yield-to-tensile ratio ≤0.78, elongation after fracture ≥20%, longitudinal impact energy value ≥100J at -20℃, and transverse impact energy value ≥80J at -20℃.
2. A method for producing Q420 grade hot-rolled H-beams with low-temperature impact resistance of -20℃ as described in claim 1, characterized in that, The production method includes the following process flow: Billet heating → billet rolling → universal precision rolling → air cooling.
3. The production method according to claim 2, characterized in that, The billet heating process involves heating the billet in the furnace at a temperature of 1235℃ to 1265℃ in the heating section and 1225℃ to 1255℃ in the soaking section, with the soaking section temperature lasting for 35 min to 55 min and the furnace time being 150 min to 180 min.
4. The production method according to claim 2, characterized in that, The billet rolling process involves an initial rolling temperature of 1150℃ to 1180℃ and a final rolling temperature of not less than 1100℃. The entire billet rolling stage achieves a cross-sectional compression ratio of 30% to 40% and a flange compression ratio of 50% to 70%.
5. The production method according to claim 2, characterized in that, The universal finishing mill: the initial rolling temperature does not exceed 1100℃, and the flange thickness is compressed by 30%~50% of the billet flange thickness throughout the finishing mill stage.
6. The production method according to claim 2 or 5, characterized in that, The universal finishing mill: the rolling speed range of the first 45% or more flange reduction passes in the universal rolling stage is 2.5~3.5m / s, the rolling speed range of the middle 40% or more flange reduction passes is 4.5~5.5m / s, and the temperature of not less than 15% of the flange reduction in the reduction passes is controlled within the range of 920~950℃, and the rolling speed range of the last 15% or less flange reduction passes is 2.5~3.5m / s.
Citation Information
Patent Citations
420 MPa grade high-performance anti-shock H-type steel and preparation method thereof
CN105018839A
420 MPa-grade H-shaped steel and preparation method thereof
CN105401075A
Thick-specification high-strength weather-resistant anti-seismic hot-rolled H-shaped steel for building steel structure
CN115725901A
Hot-rolled H-shaped steel with yield strength of 550MPa and longitudinal and transverse low-temperature impact toughness of-20 DEG C and production method thereof
CN115161553A
Economical 550MPa hot-rolled H-shaped steel for ultra-deep well derrick and production method
CN116334475A